(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The sedimentary record of the Andean orogenic basins in the Calchaquies Valleys (Fig. 1), consists of nearly 6000 m of an overall coarsening and thickening upward clastic succession (Díaz and Malizzia, 1983) known as the Payogastilla Group. The Payogatilla Group is composed of the Quebrada de losColorados, Angastaco, Palo Pintado and San Felipe Formations (Díaz and Malizzia, 1983; Díaz et al., 1987 - see Fig. 2). Our investigation and previous research in the Quebrada de losColorados Formation (e.g. Galli and Hernández, 1999; Coutand et al., 2006; Carrapa et al., 2011a,b; Galli et al., 2011) allowed the identification of several unconformity surfaces, including an angular relationship between the Quebrada de losColorados Formation and the underlying Salta Group. Moreover, the identification of an intra-formational unconformity led us to the reconsideration of the stratigraphic scheme of the Payogastilla Group. Here, we address the regional stratigraphic relations of the Quebrada de losColorados Formation, the lower unit of the Payogastilla Group, in order to update the knowledge and to discuss the validity of the present stratigraphic framework. Along the Calchaquies Valleys, the Quebrada de losColorados Formation rests on different units of the Salta Group. The more frequent relation is with the uppermost unit, the Lumbrera Formation (Fig. 3), but in some areas, for example at Saladillo, the Quebrada de losColorados Formation rests in angular relationship on the Maíz Gordo Formation (del Papa et al., 2004), as in the Esquina Azul locality (Fig. 4). In the cerroBayo site, the Quebrada de losColorados Formation lies also upon the Maíz Gordo Formation but few meters laterally directly overlays the Mealla Formation (Figs. 2 and 4). In other places, like in the Pucará valley (Fig. 1), the Quebrada de losColorados overlays the Pirgua Subgroup (Villanueva García, 1992; Sabino, 2004). These variable stratigraphic relationships are key features that document the tectonic inversion of the Salta Group contemporaneous with the Quebrada de losColorados sedimentation. The Quebrada de losColorados Formation consists of red fine-grained floodplain facies and sandy to gravelly clastic fluvial channels facies (Fig. 6). The original description of this unit includes an eolian succession in the upper section (Díaz and Malizzia, 1983). In some localities, like at Tin Tin and Tonco (Fig. 1), the eolian and fluvio-eolian successions have thicknesses ranging from 450 to 600 m (Starck and Vergani, 1996; del Papa et al., 2013) representing a very distinctive erg record. The contact with the underlying fluvial deposits is sharp and a calcretepaleosol (Fig. 5) is locally recognized suggesting the presence of an unconformity within the Quebrada de losColorados Formation. Moreover, this fluvio-eolian succession has a transitional contact with the overlying fluvial conglomeratic facies of the Angastaco Formation. This stratigraphic relation suggests that the former could be formally included within the Angastaco Formation. Thus we propose a redefinition of the Angastaco Formation (Díaz and Malizzia, 1983; nom. transl. Díaz et al., 1987); including the fluvio-eolian succession as the basal Tin Tin Member and to return to the previously defined Las Flechas Member. We propose the Tin Tin area (25º13’51.6’’ Lat. S and 66º00’58.5’’ Log. W - 25°16’12’’ Lat. S and 66°2’39.45’’ Log. W) as stratotype area (Fig. 7). In this locality, pale red silty sandstones to siltstones overlie coarse conglomeratic strata (Figs. 5 and 6) and are overlain by white eolian sandstones that grade to gray conglomeratic strata of the Angastaco Formation sensuDíaz and Malizzia (1983). The age of the Tin Tin Member is considered late Oligocene to early Miocene according to the 21 Ma U/Pb zircon datings (Carrapa et al., 2011a; del Papa et al., 2013). Finally we propose the Quebrada Grande loca- lity (25º12’59.1’’ Lat. S and 66º01’33.1’’ Log. W), along state route Nº 42, Tin Tin area, Calchaquí Valley (Fig. 7) as hypostratotype of the Quebrada de losColorados Formation. In this locality, this unit rests unconformably, and locally through an angular unconformity, on the Lumbrera Formation (Salta Group, Figs. 2, 3 and 4). In this area the formation is 792 m thick and is characterized by two coarsening upward successions of red siltstone, lenticular to shallow lenticular coarse sandstones and horizontally stratified conglomerates (Fig. 5). Based on mammalian biostratigraphy recorded at sites in Cerro Bayo, Tin Tin and Luracatao (Fig. 1) the age of the Quebrada de losColorados Formation is Casamayoran (sub-age Barrancan), SALMA, sugges- ting a Middle Eocene age for the basal levels (Powell et al., 2011). In summary, we propose that the fluvio-eolian section of the Quebrada de losColorados Formation should be incorporated into the Angastaco Forma- tion, as the Tin Tin Member. This modification will simplify recognition in the field, mapping, and genetic interpretation of these foreland basin deposits.